The political dimension of history in the work of Hannah Arendt (Praxis Educativa, 2012)
The aim of this paper is to analyze the similarities in terms of historical conceptions between Hannah Arendt and Arthur Danto. On the basis of those similarities, and in view of the fact that the works of Arendt related to this subject were published before those of Danto- middle and late 50s- we will try to show how this authoress anticipated, in a certain way, the general approach of historical narrativism that began with Dantoís publication in 1965 of his book “Filosofía analítica de la historia”. We also consider that, unlike Danto, Arendt deals not only with the epistemological issues of History but also with the relationship between History and Politics. This particular aspect in Arendt’s approach, that we will call the political dimension of History, plays a key role in the strengthening of the public sphere.
Keywords: history; story; action; politics; public sphere